2021
DOI: 10.2196/29749
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Machine Learning in Diagnosing Bipolar Disorder: Scoping Review

Abstract: Background Bipolar disorder (BD) is the 10th most common cause of frailty in young individuals and has triggered morbidity and mortality worldwide. Patients with BD have a life expectancy 9 to 17 years lower than that of normal people. BD is a predominant mental disorder, but it can be misdiagnosed as depressive disorder, which leads to difficulties in treating affected patients. Approximately 60% of patients with BD are treated for depression. However, machine learning provides advanced skills and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 53 publications
2
28
0
Order By: Relevance
“…The prevalence of type 1 bipolar disorder in the general population is 1.5-2.1% and in the intensive care unit (ICU) is 21-26% [5][6][7][8]. The aggregate lifetime prevalence of all types of bipolar disorder was reported to be 5% [9].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of type 1 bipolar disorder in the general population is 1.5-2.1% and in the intensive care unit (ICU) is 21-26% [5][6][7][8]. The aggregate lifetime prevalence of all types of bipolar disorder was reported to be 5% [9].…”
Section: Introductionmentioning
confidence: 99%
“…In psychiatry, NLP can be used for IE from unstructured EHR and speech analysis on patient speech data [63,64]. NLP can help in the screening, early diagnosis, or severity estimation of various diseases such as depression [63], bipolar disorder [65], dementia [66][67][68], psychosis [69,70], and schizophrenia [71]. Dai…”
Section: Psychiatrymentioning
confidence: 99%
“…Due to their nature, they were not categorized into any of the three topics presented in Section "Results." Some of these reviews are extremely focused on a specific argument (6)(7)(8)(9)(10); this makes them good candidates for topic-specific analysis, but they lack a general vision. Other reviews do not present the breakthroughs of the last 4-5 years (attention mechanism, transformers, BERTmodels, etc.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, researchers have recognized that social medias can also be a source of text for these experiments. This is the case of Low et al ( 67 70) exploited data from Reachout.com, 7 an online mental health service for young people and their parents in Australia, benchmarking multiple methods of text feature representation for social media posts and comparing their downstream use with automated ML tools. Yu et al (71) used data from the John Tung Foundation 8 to build a framework for discovering linguistic association patterns, and showed that they are promising features for classification tasks.…”
Section: Natural Language Processing For Classificationmentioning
confidence: 99%